Residual cancer lymphocytes in patients with chronic lymphocytic leukemia after therapy show increased expression of surface antigen CD52 detected using quantitative fluorescence cytometry - Pevna, Michaela; Doubek, Michael; Coupek, Petr; Stehlikova, Olga; Klabusay, Martin (Clinical lymphoma, myeloma & leukemia, 2014)
BACKGROUND: Rituximab and alemtuzumab, mAbs used in recent years to treat CLL, are directed against antigens CD20 and CD52. CD20 is not highly expressed by CLL tumor cells, and rituximab does not have significant effectiveness in CLL unless combined with chemotherapy. Alemtuzumab targets CD52, which is much more highly expressed, and is currently the most effective agent used alone for CLL. Variability in expression of both antigens among these patients might be related to different individual therapeutic responses to mAb therapy. PATIENTS AND METHODS: A total 95 patients diagnosed with CLL and/or SLL were divided into 4 groups: (1) untreated; (2) in complete or partial remission; (3) disease in progression; and (4) diagnosed with SLL. Flow cytometry of peripheral blood cells included gating of the CD5(+)CD19(+) tumor population, within which mean fluorescence intensity of fluorescein isothiocyanate (FITC) conjugated with anti-CD20 or anti-CD52 antibody was measured. The resulting expression of the 2 antigens was deduced from the calibration curve using Quantum FITC particles. RESULTS: Expression of CD20 showed no significant differences among the 4 groups of patients. However, significantly greater expression of surface antigen CD52 was recorded in patient group 2 in complete or partial remission (P < .001). CONCLUSION: The residual population of CLL cells after therapy is characterized by increased surface detection of CD52. Although the exact cause of this phenomenon is unknown, our results provide a basis to consider the potential for CLL consolidation therapy using alemtuzumab.
Keywords: indukce remise; Patient Selection; Lymphocytes; lymfocyty; Remission Induction; Fluorometry; kalibrace; lidé; Antibodies, Monoclonal, Humanized; senioři nad 80 let; fluorescein-5-isothiokyanát; Antigens, CD; senioři; humanizované monoklonální protilátky; cílená molekulární terapie; průtoková cytometrie; chronická lymfatická leukemie; Calibration; mužské pohlaví; CD antigeny; protokoly protinádorové kombinované chemoterapie; Female; Adult; fluorometrie; Fluorescein-5-isothiocyanate; Molecular Targeted Therapy; Male; Antigens, Neoplasm; glykoproteiny; Aged, 80 and over; ženské pohlaví; dospělí; Glycoproteins; Leukemia, Lymphocytic, Chronic, B-Cell; Aged; Flow Cytometry; fluorescenční barviva; Antineoplastic Combined Chemotherapy Protocols; Humans; lidé středního věku; Middle Aged; reziduální nádor; Neoplasm, Residual; Fluorescent Dyes; výběr pacientů; antigeny nádorové